NON-MOTOR MANIFESTSTIONS OF PARKINSON’S DISEASE: GENDER DIFFERENCES AND CORRELATIONS WITH MOTOR PHENOMENA - Genyk S.І.; Gryb, V.A.; Doroshenko, O.O.; Maksymchuk, L.T.; Genyk, S.M.; Genyk, Ya.I. (World of Medicine and Biology, 2019)
Parkinson’s disease (PD) is characterized by a wide range of non-motor symptoms (NMS), the evaluation of which can help in the differential diagnosis of various types of parkinsonism. There are increasing reports of gender and age differences in NMS PD and their special relationship with motor phenomena. 44 elderly patients (60-74 years) were surveyed, who had the most pronounced NMS according to the unified PD assessment scale (UPDRS) (related to PD, but not with other illnesses), without motor complications, who additionally were performed a status assessment using Non-Motor Symptom assessment scale for Parkinson’s Disease (NMS-PD). In assessing NMS, we found a significant increase in their indicators in the main group compared with the control group. Thus, the total NMS-PD score in the male group was 136 (92; 150), in the group of women - 172 (133; 172) (p = 0.038), and accordingly, 8.5 (16 ( 8; 19), p = 0.002) and 13.2 (13 (8; 15), p = 0.002) times higher than the indicators in the control groups. When analyzing the NMS-PD scale for domains, we found their indicators growth compared with the control group. In the group of men, the difference was found in the domains of "sleep / fatigue" (p = 0.005), "mood / cognition" (p = 0.005), "gastrointestinal tract" (p = 0.000), "urination" (p = 0.000), "sexual function" (p = 0.000) and "different" (p = 0.000); in the group of women - "sleep / fatigue" (p = 0.000), "mood / cognition" (p = 0.000), attention / memory "(p = 0.003)," gastrointestinal tract "(p = 0.000) , "urination" (p = 0.000), "sexual function" (p = 0.000) and "different" (p = 0.005). In addition, the indicator "urination" in the group of women was significantly increased compared with the group of men (p = 0.003). According to the 2nd domain of the UPDRS scale (motor aspects of daily activity), in the male group it was 22 (21; 35), in the group of women - 21 (21; 30) (p> 0.05). In order to detect the relationship between motor and non-motor phenomena of PD, a Spearman rank coefficient calculation was performed. In general, the relationships were negative, and the most significant were for the following indicators: in the group of men - "cardiovascular disorders including falls", "sleep / fatigue", "sexual function", "different", in the group of women - "mood / cognition", "gastrointestinal tract", "urination". Conclusions. Gender differences in the incidence and peculiarities of the PD course are likely to be related to sexual dimorphisms, formed as a result of hormonal influences, and require further research. The spectrum of NMS in different sex groups with PD is approximately the same. However, in women disturbances of attention and memory are additionally observed, and urination is more disturbed than in men. We believe that the patients we examined suffered from a specific subtype of PD with predominance of NMS, requiring a separate approach to diagnosis and treatment. In-depth study of gender differences in NMS of PD in other age groups and in more patient samples is necessary. The study of NMS as a separate subtype that needs a peculiar approach (not as an additional phenomenon of PD) should also be continued.